Atypical surface behavior of ceramides with nonhydroxy and 2-hydroxy very long-chain (C28-C32) PUFAs - Peñalva, Daniel Alejandro (2013)
Unique species of ceramide (Cer) with very-long-chain polyunsaturated fatty acid (VLCPUFA), mainly 28?32 carbon atoms, 4?5 double bonds, in nonhydroxy and 2-hydroxy forms (n-V Cer and h-V Cer, respectively), are generated in rat spermatozoa from the corresponding sphingomyelins during the acrosomal reaction. The aim of this study was to determine the properties of these sperm-distinctive ceramides in Langmuir monolayers. Individual Cer species were isolated by HPLC and subjected to analysis of surface pressure, surface potential, and Brewster angle microscopy (BAM) as a function of molecular packing. In comparison with known species of Cer, n-V Cer and h-V Cer species showed much larger mean molecular areas and increased molecular dipole moments in liquid expanded phases, which suggest bending and partial hydration of the double bonded portion of the VLCPUFA. The presence of the 2-hydoxyl group induced a closer molecular packing in h-V Cer than in their chain-matched n-V Cer. In addition, all these Cer species showed liquid-expanded to liquid-condensed transitions at room temperature. Existence of domain segregation was confirmed by BAM. Additionally, thermodynamic analysis suggests a phase transition close to the physiological temperature for VLCPUFA-Cers if organized as bulk dispersions.